2022
DOI: 10.1039/d1lc01077h
|View full text |Cite
|
Sign up to set email alerts
|

3D printed microfluidic devices for lipid bilayer recordings

Abstract: This paper verifies the single-step and monolithic fabrication of 3D structured lipid bilayer devices using stereolithography. Lipid bilayer devices are utilized to host membrane proteins in vitro for biological assays...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Here, we introduced the step to control the direction of bubbles but also considered the use of a hydrophobic/hydrophilic patterning of the surfaces that would similarly guide the bubbles by the surface tension forces. However, we avoided the negative influence of the surface modification on the formation process of BLM, 41 where infusions of both aqueous solution and organic solvent into the wells are mandatory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we introduced the step to control the direction of bubbles but also considered the use of a hydrophobic/hydrophilic patterning of the surfaces that would similarly guide the bubbles by the surface tension forces. However, we avoided the negative influence of the surface modification on the formation process of BLM, 41 where infusions of both aqueous solution and organic solvent into the wells are mandatory.…”
Section: Resultsmentioning
confidence: 99%
“…To verify the BLM reformation with air bubbles, a 4ch device was fabricated using a three‐dimensional printer (XFAB3500; DWS) 41 . The device design was the same as the one above.…”
Section: Methodsmentioning
confidence: 99%
“…Several groups have reported the integration of nanopores within microfluidic architectures for high-throughput detection of nanoparticles. Varongchayakul et al presented a standalone microfluidic-nanopore setup that supports on-chip sample preparation, purification, and single-molecule nanopore measurements (Figure E) . With the recent development in 3D-printing technology, nanopore supports and microdevices with custom features can now be tailored in a rapid and facile manner, favoring their integration in miniaturized setups. Roman et al reported a PDMS-based microfluidic device with an integrated nanopore utilizing 3D-printed molds …”
Section: High-throughput Nanoporesmentioning
confidence: 99%
“…[72][73][74] Varongchayakul et al presented a standalone microfluidic-nanopore setup that supports on-chip sample preparation, purification and singlemolecule nanopore measurements (Figure 1E). 64 With the recent development in 3D-printing technology, nanopore supports and microdevices with custom features can now be tailored in a rapid and facile manner, 75 favoring their integration in miniaturized setups. Roman et al reported a PDMS-based microfluidic device with integrated nanopore utilizing 3D-printed moulds.…”
Section: Integration Modalities For Nanoporesmentioning
confidence: 99%